International trade with equilibrium unemployment - Davidson, Carl, 1957- (Princeton University Press, 2010)
While most standard economic models of international trade assume full employment, Carl Davidson and Steven Matusz have argued over the past two decades that this reliance on full-employment modeling is misleading and ill-equipped to tackle many important trade-related questions. This book brings together the authors' pioneering work in creating models that more accurately reflect the real-world connections between international trade and labor markets. The material collected here presents the theoretical and empirical foundations of equilibrium unemployment modeling, which the authors and the.